2019
DOI: 10.1159/000494462
|View full text |Cite
|
Sign up to set email alerts
|

Low Renal Oxygen Saturation at Near-Infrared Spectroscopy on the First Day of Life Is Associated with Developing Acute Kidney Injury in Very Preterm Infants

Abstract: Background: Acute kidney injury (AKI) is a frequent complication in preterm infants, and the identification of early markers of renal hypoperfusion is a chief challenge in neonatal intensive care units. Objectives: To describe the association between early markers of cardiovascular function and renal perfusion with AKI occurrence in a cohort of preterm infants < 32 weeks’ gestation. Methods: 128 infants were prospectively included from birth to discharge. During the first day of life, we assessed cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 20 publications
2
39
0
1
Order By: Relevance
“…The low renal rSO 2 levels were found to be associated with high serum creatinine values in the second to seventh days. 1 In our study, the low renal rSO 2 in the first hour of life was associated with high SCr values on the second to fourth days. Low renal rSO 2 values were found to be below the normal values reported in the literature.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The low renal rSO 2 levels were found to be associated with high serum creatinine values in the second to seventh days. 1 In our study, the low renal rSO 2 in the first hour of life was associated with high SCr values on the second to fourth days. Low renal rSO 2 values were found to be below the normal values reported in the literature.…”
Section: Discussionsupporting
confidence: 54%
“…5 The common pathophysiology in the neonatal AKI development is renal hypoperfusion and hypoxia. 1,2 Understanding the factors that cause this and determining this situation will enable the prediction of AKI development. The inhibition of AKI development will also improve the rates of mortality and morbidity of these vulnerable infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study with preterm pigs, we demonstrated for the first time that CA, induced by IA LPS exposure, resulted in renal inflammation both at birth and 5 days after preterm birth with the involvement of innate and adaptive immune activation. Our data imply that prenatal insults may play a critical role in determining neonatal kidney outcomes and may explain the high incidence of AKI in preterm infants (46,(57)(58)(59)(60), although reduced gestational age at birth is also a risk factor (61).…”
Section: Discussionmentioning
confidence: 75%